Chemometric Optimization of Online SPE-LC Method Using Polypyrrole-Graphene Oxide Sorbent for Tetracycline Analysis in Water Samples - Zaini, Nurzaimah; Jawad, Ali H.; Hanapi, Nor Suhaila Mohamad; Yahaya, Noorfatimah; Anis, Ahmad Lutfi; Kamaruzaman, Sazlinda; Ibrahim, Wan Nazihah Wan (Trends in Sciences, 2025)
A novel automated analytical method integrating online solid-phase extraction with liquid chromatography (online-SPE-LC) with chemometrically optimization was developed for the rapid and sensitive quantification of five selected tetracycline antibiotics, namely oxytetracycline, tetracycline, demeclocycline, chlortetracycline and doxycycline in water samples. In this method, a green polypyrrole-graphene oxide (PPy-GO) composite was employed as extraction sorbent. The effects of flow rate, valve switching time, sorbent mass, solvent composition and buffer pH were investigated using half-fraction Central Composite Design (CCD) of Response Surface Methodology (RSM). Optimal conditions were determined to be a solvent flow rate of 0.75 mL min⁻¹, valve switching time of 1.6 min, sorbent mass of 55 mg, solvent composition of 80:20 (ACN:water), and buffer pH of 2.5. The optimized method exhibited excellent linearity (R2 = 0.9990-0.9997) across a wide concentration range (10-1000 µg L−1) with low limits of detection (3.2 - 6.7 µg L−1). Method precision and accuracy were demonstrated by recoveries ranging from 82% - 102% and relative standard deviations (RSDs) of 0.6% - 3.0% (n=3) in both river and tap water samples. Compared to existing approaches, the developed method shows superior selectivity, high sensitivity, rapid and automation. Thus, this study highlights the great potential of PPy-GO as efficient sorbent integrated with online -SPE-LC method for the extraction of tetracycline from water samples. HIGHLIGHTS A novel study using chemometrically Optimized Fully Automated Online-SPE-LC Method with Polypyrrole- Graphene Oxide as Sorbent toward tetracyclines antibiotics in water samples. Synthesis and Characterization of PPy-GO sorbent. Using Chemometric (BBD) optimization with fully automated online SPE-LC for tetracycline analysis in water samples using PPy-GO sorbent. The integrated system by Online SPE coupled with Liquid Chromatography as rapid developing technique for the analysis of tetracyclines antibiotics in water samples. Modern trend of extraction techniques for pharmaceutical analysis. GRAPHICAL ABSTRACT